Metabolismos do nitrogênio, do carbono e antioxidante em plantas jovens de Ipê-Felpudo (Zeyheria Tuberculosa) cultivadas em excesso de ferro e manganês - Torres, Taís (2021)
The mining sector has an undeniable importance for the Brazilian economy. However, this activity produces a large amount of waste potentially harmful to the environment. An example of this was the collapse of the Fundão dam (Mariana/MG) in November 2015, where rivers and hundreds of kilometers of areas adjacent to the Rio Doce basin were contaminated with tailings, composed of high concentrations of trace elements, among which, Fe and Mn were found in larger quantities. Species such as Zeyheria tuberculosa (Vell.) Bureau ex Verl., better known as Ipê-felpudo, are a good alternative for revegetation of areas contaminated by mining because it is a native species, initial secondary to the succession group ecological and with ruderal characteristics. Thus, the objective of this work was to evaluate the effects of excess Fe and Mn on nitrogen, carbon and antioxidant metabolisms in young ipe-fery plants. Plants were grown in pots filled with sand, irrigated with complete nutrient solution (CNS) (BOLLE-JONES, 1957), – CNS (control), CNS with excess iron – 0.160 mM (+ Fe), CNS with excess manganese – 0.327 mM (+ Mn) and CNS with excess iron and manganese – 0.160 mM + 0.327 mM (+ Fe + Mn). The experimental design used was completely randomized, totaling 4 treatments and 6 replications. Data were subjected to analysis of variance (ANOVA) and Tukey's test at 5% significance in the R® software. The activities of enzymes involved in nitrogen metabolism (NR, GS, GOGAT and GDH) and the antioxidant system (SOD, CAT and APX), photosynthetic parameters, growth parameters, concentrations of chlorophylls and carotenoids, quantification of carbohydrates, proteins and amino acids, in addition to the quantification of nitrogen, iron and manganese contents in the plants, were evaluated. Excess iron caused symptoms of toxicity, evidenced by decreased root length, reduced pigment content and photosynthetic efficiency, increased H2O2 in leaves and reduced carbohydrates in roots, which were not observed in treatments with excess manganese. In plants under high concentrations of both iron and manganese, changes in nitrogen metabolism, protein degradation and increase in free amino acids, reduction in soluble and reserve carbohydrates, increased enzyme activity of the antioxidant system and damage oxidative in the leaves were observed. The excess of Mn proved to be less harmful, in addition to having mitigated the toxic effects caused by excess iron in most of the physiological parameters evaluated, suggesting that this species has promising potential to be used in the recovery of soils contaminated by tailings containing concomitantly Fe and Mn in the previously reported concentrations.